Interactive E-LKPD Based on PjBL: Innovation Learning Adaptive for Improving Learning Outcomes Student Class X - Sabari, Sabari; Firdaus, Rangga (STKIP Al Islam Tunas Bangsa dan HEPI, 2025)
The digital era demands the integration of innovative learning media to develop 21st century skills. This study aims to develop E-LKPD-based learning media combined with the Project-Based Learning (PjBL) model to improve learning outcomes, motivation, and collaboration, creativity, and problem-solving skills. The research used the ADDIE development model and was applied to class X students of SMA Negeri 2 Metro. The results showed that the use of PjBL-based E-LKPD significantly improved learning outcomes, with an average increase of 20 points and a p-value of 0.002. The N-gain value of the experimental group reached 0.78 (high category), while the control group was only 0.28 (low category). The effect size value of 1.3 indicates the large influence of the media on improving learning outcomes. 21st century skills also improved, with an average score of 4.2 in the experimental group compared to 3.1 in the control. As many as 85% of students stated that they were more enthusiastic and independent when learning. These findings indicate that the PjBL-based E-LKPD media is effective in supporting active learning, improving understanding, and shaping 21st century essential competencies. The implication of this research is the importance of integrating technology-based learning media to support independent learning curriculum, improve learning quality, and encourage active student engagement. Project-based learning and digital media can provide alternatives for teachers to be more effective in developing students' potential in an ever-evolving world.